Preinjury Palliative Performance Scale predicts functional outcomes at 6 months in older trauma patients. Issue 3 (September 2019) - Hwang, Franchesca; Pentakota, Sri Ram; McGreevy, Christopher M.; Glass, Nina E.; Livingston, David H.; Mosenthal, Anne C.
Abstract : BACKGROUND: Older trauma patients have increased risk of adverse in-hospital outcomes. We previously demonstrated that low preinjury Palliative Performance Scale (PPS) independently predicted poor discharge outcomes. We hypothesized that low PPS would predict long-term outcomes in older trauma patients. METHODS: Prospective observational study of trauma patients aged ≥55 years admitted between July 2016 and April 2018. Preinjury PPS was assessed at admission; low PPS was defined as 70 or less. Primary outcomes were mortality and functional outcomes, measured by Extended Glasgow Outcome Scale (GOSE), at discharge and 6 months. Poor functional outcomes were defined as GOSE score of 4 or less. Secondary outcomes were patient-reported outcomes at 6 months: EuroQol-5D and 36-Item Short Form Survey. Adjusted relative risks (aRRs) were obtained for each primary outcome using multivariable modified Poisson regression, adjusting for PPS, age, race/ethnicity, sex, and injury severity. RESULTS: In- hospital data were available for 516 patients; mean age was 70 years and median Injury Severity Score was 13. Thirty percent had low PPS. Six percent (n = 32) died in the hospital, and half of the survivors (n = 248) had severe disability at discharge. Low PPS predicted hospital mortality (aRR, 2.6; 95% confidence interval [CI], 1.2–5.3) and poor outcomes at discharge (aRR, 2.0; 95% CI, 1.7–2.3). Six-month data were available for 176 (87%) of 203 patients who were due for follow-up. Functional outcomes improved in 64% at 6 months. However, 63% had moderate to severe pain, and 42% moderate to severe anxiety/depression. Mean GOSE improved less over time in low PPS patients (7% vs. 24%; p < 0.01). Low PPS predicted poor functional outcomes at 6 months (aRR, 3.1; 95% CI, 1.8–5.3) while age and Injury Severity Score did not. CONCLUSION: Preinjury PPS predicts mortality and poor outcomes at discharge and 6 months. Despite improvement in function, persistent pain and anxiety/depression were common. Low PPS patients fail to improve over time compared to high PPS patients. Preinjury PPS can be used on admission for prognostication of short- and long-term outcomes and is a potential trigger for palliative care in older trauma patients. LEVEL OF EVIDENCE: Prognostic study, Therapeutic level IV.